2016
DOI: 10.1177/0040517515609254
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and optimization of ends-together pneumatic splice chambers

Abstract: Pneumatic splice chambers are the industry method for splicing yarns. Most investigations in the literature occurred with ends-opposed splice chambers. For several applications, ends-together splicing is industrially interesting to consider. In this paper, we determine the importance of some process and splice chamber design parameters for ends-together splice chambers. We find that splicing pressure can be maximized, splicing duration needs to exceed a minimum duration and optimum splice length depends on yar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…By extending the cutting position by 1.5 or 3 mm we observe higher strength at inlet pressure of 15 bar than at inlet pressure of 10 bar for all chambers. In De Meulemeester et al, 11 it was found that splice strength increases rapidly from zero after a certain minimum pressure, but then often reaches a plateau after which the strength no longer increases. For chambers 1 and 3 the splice strength reached a maximum at 12 bar, while the splice strength in chamber 2 kept increasing all the way up to the maximum achievable pressure of 15 bar.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…By extending the cutting position by 1.5 or 3 mm we observe higher strength at inlet pressure of 15 bar than at inlet pressure of 10 bar for all chambers. In De Meulemeester et al, 11 it was found that splice strength increases rapidly from zero after a certain minimum pressure, but then often reaches a plateau after which the strength no longer increases. For chambers 1 and 3 the splice strength reached a maximum at 12 bar, while the splice strength in chamber 2 kept increasing all the way up to the maximum achievable pressure of 15 bar.…”
Section: Resultsmentioning
confidence: 97%
“…The resulting average splice strength of 20 samples, as in De Meulemeester et al, 11 is listed in Tables 2 and 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the experimental study performed by Baykaldi et al, 8 the breaking strength was found to be affected by splicing air pressure, splicing duration, twist factor, and linear density for cotton/elastane yarns, and the parameters that affected breaking elongation and the diameter of the spliced yarn are the inlet air pressure and twist factor. De Meulemeester et al 9 concluded that a high strength spliced joint was the consequence of maximum air inlet pressure, minimum splicing duration, and optimized chamber structure by employing a Design of Experiment (DOE) method. Although those works have been done to facilitate optimizing the configuration parameters of the splicing process, they lack direct understanding of the filament motion.…”
mentioning
confidence: 99%